EDUKASI PENGELOLAAN KEUANGAN PADA USIA DINI DI PONDOK PESANTREN INSAN MULIA LAMPUNG TENGAH - Wuryanti, Lestari; Rahyono, Rahyono; Fatih, Muhammad Al; Robani, Sholahuddin; Nurdiansyah, Ridho (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2023)
The Financial management education activities at an early age were carried out at the Insan Mulia Islamic Boarding School, Tanggul Angin Village, Punggur District, Central Lampung Regency. This activity is an effort and concern for early age education efforts for students who are future generations. This study uses primary data taken directly when meeting students as participants. This study also uses secondary data as supporting data or references in an effort to fulfill the information in this study. This activity is carried out as a step so that students can manage their finances, and can use their money for more planned expenses. This is done so that the students' monthly pocket money needs can be met, there is no waste or shortage, which allows students to borrow or go into debt. Based on the findings in this study, there are students who are already able to manage their finances, but there are still students who are not able to manage their finances. This education is expected to be an additional knowledge for students in managing their finances so that they can organize and plan their financial use optimally.